المقومات البديلة للاستثمار الفكري في إدارة الموارد المعرفية (عرض انتقادي لأفكار ومقاربات منهجية) - عزي, الأخضر; ثابتي, الحبيب (Sciences humaines; Vol. 30 (2013): SCIENCES HUMAINES)
يتميّز محيط الأعمال، في هذه المرحلة الحساسة من تاريخ المجتمعات البشرية، بتحولات جذرية و تغيّرات عميقة، انقلبت بموجبها كل الموازين تقريبا و توجب بسببها إعادة النظر و مراجعة كل المفاهيم و القناعات الراسخة. و يمكن اعتبار أهم انقلاب في هذا المضمار هو انتقال مركز الثقل و مرتكز النمو من المقدرات المادية و المالية إلى المقدرات المعرفية و الإبداعية، و هو ما يطرح اليوم نموذجا تحليليا جديدا Un Nouveau Paradigme في مجال التنظيم و الإدارة الإستراتيجية للمؤسسات الاقتصادية. تطرح هذه الورقة إشكالية الرهان على الاستثمار في الموارد غير المادية و سبل الارتقاء بمؤسساتنا الاقتصادية إلى مستوى حيازة القدرات  التنافسية التي تستجيب لمتطلبات المرحلة الراهنة؛ لتصل من خلال ذلك إلى استكشاف أهم المقومات البديلة لمواجهة لتحديات التنافسية الجديدة.    The radical transformations and the rapid changes constitute the principal characteristics of the actual economic environment. This new situation has confused the sum of convictions and imposed the act of revising and overseeing of all work organization’s methods inherited from the qualified period of the industrial society. The actual passage towards the society of knowledge and the conditions, that such a mutation demands, replaces the immaterial resources in the centre of every strategic réflexion. This opens the way for a new paradigm to spring up and constitutes a revaluation of knowledge and competences which are actually considered as major conditions for firm’s survival and competitiveness. The present article attempt to prospect the consequences of such a  change and to highlight the conditions and the methods of conception and the adoption of strategies based upon immaterial investment and the knowledge management.